Scrub Typhus in the Torres Strait Islands of North Queensland, Australia - Antony G. Faa; William J.H. McBride; Gaynor Garstone; Robert E. Thompson; Peter Holt (Emerging Infectious Diseases, 2003)
Scrub typhus, caused by Orientia tsutsugamushi, occurs throughout Southeast Asia. We descript ten cases that occurred in the Torres Strait islands of northern Australia during 2000 and 2001. Preceding heavy rain may have contributed to the outbreak. The successful use of azithromycin in two pediatric patients is also reported.